Penerapan Media Puzzle Sebagai Alternatif Penguasaan Bilangan dan Angka di Kelas II SD Negeri 137 Palembang - Niken Veronika; Ramanata Disurya; Tanzimah Tanzimah (Departement of Mathematics Education, 2023)
A media puzzle is a media that combines an image and a puzzle where the way to play is to combine a piece of a pattern or image so that it becomes a pattern unit which is the key to the answer. This study aims to determine the effect of applying the media puzzle as an alternative to mastery of numbers and numbers. This study uses experimental research, the method used is experimental design with a type one-group pretest-posttest design. The sample used was all grade II students at SD Negeri 137 Palembang. Before conducting the hypothesis test, the prerequisite test was carried out in this study, namely the normality test and homogeneity test and it was stated that the distribution was normal and homogeneous, the hypothesis test was carried out using the t test, namely the paired sample t test. The results of testing the hypothesis obtained a significant value on the test-retest and posttest ie 10.329 where ttable= 1.796 with df = n-2 where n = 13 so df = 11 with the levels α = 0.05, so it can be concluded tcount= 10.329 ≥ ttable= 1,796 eyes Ha accepted H0 rejected, or the influence of the application of the media puzzle as an alternative to mastery of numbers and numbers in class II SD Negeri 137 Palembang